Preparation and Adsorption Properties of Magnetic Molecularly Imprinted Polymers for Selective Recognition of 17β-Estradiol - Lanbo Bi; Jimin Shen; Zhuoran Yao; Jing Kang; Shengxin Zhao; Pengwei Yan; Binyuan Wang; Zhonglin Chen (Separations, 2022)
In this paper, magnetic molecularly imprinted polymers (MMIPs) were fabricated on the surface of Fe3O4 by surface molecular imprinting technology, which can selectively adsorb 17β-estradiol (E2). The optimized experiments demonstrated that MMIPs possessed the best adsorption capacity when methanol was used as the solvent and MAA was used as the crosslinking agent, with a molar ratio of E2: MMA: EGDMA as 1:4:50. SEM, FTIR, and XRD were employed to investigate the morphologies of MMIPs and the results demonstrated that the MMIPs that can selectively adsorb E2 were successfully prepared on Fe3O4 particles. The adsorption experiments showed that 92.1% of E2 was adsorbed by the MMIPs, which is higher than the magnetic non-molecularly imprinted polymers (MNIPs). The Freundlich isotherm model was more suitable to describe the adsorption process of E2 by MMIPs. Meanwhile, MMIPs had a better recognition ability for E2 and its structural analogs such as estrone and estriol. The MMIPs still had good adsorption performance after methanol regeneration five times. The prepared MMIPs had the advantages of efficient adsorption ability and high reusability, so they can be applied for selective recognition and removal of E2.